An unusual case of Cervical intramedullary neurocysticercosis mimicking ependymoma - Phuyal, Suman; Rajbhandari, Binod; Sedain, Gopal; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2018)
Neurocysticercosis is a common parasitic infection of the central nervous system, caused by larvae of Taeniasolium. Cysticercosis of spine is less common compared to that of brain itself. Anatomically, spinal cysticercosis can be classified as extraspinal (vertebral) or intraspinal (epidural, subdural, arachnoid, or intramedullary), where intramedullary type is extremely rare. Isolated spinal intramedullary neurocysticercosis without brain involvement is even rarer. Preoperative diagnosis of cystericosis within the cord maybe difficult; and the clinical and radiographic features may mimick that of more common intramedullary tumor. Here, we present a rare case of cervical intramedullary neurocysticercosis in an adult, presenting with progressive limb weakness, mimicking spinal ependymoma, clinically and radiographically and only diagnosed histopathologically after surgery.